The impact of perception on institutional delivery service utilization in Northwest Ethiopia: the health belief model - Adane Nigusie; Telake Azale; Mezgebu Yitayal; Lemma Derseh (BMC, 2022)
Abstract Background Ethiopia has been striving to promote institutional delivery through community wide programs. However, home is still the preferred place of delivery for most women encouraged by the community`s perception that delivery is a normal process and home is the ideal environment. The proportion of women using institutional delivery service is below the expected level. Therefore, we examined the impact of perception on institutional delivery service use by using the health belief model. Methods A community-based cross-sectional study was conducted among 1,394 women who gave birth during the past 1 year from September to December 2019. A multistage sampling technique was used to select the study participants. Data were collected by using health belief model constructs, and structured and pretested questionnaire. Binary logistic regression was performed to identify factors associated with the outcome variable at 95% confidence level. Results Institutional delivery service was used by 58.17% (95% CI: 55.57- 60.77%) of women. The study showed that high perceived susceptibility (AOR = 1.87; 95% CI 1.19-2.92), high cues to action (AOR = 1.57; 95% CI: 1.04-2.36), husbands with primary school education (AOR = 1.43; 95% CI 1.06-1.94), multiparty(5 or more) (AOR = 2.96; 95% CI 1.85-4.72), discussion on institutional delivery at home (AOR = 4.25; 95% CI 2.85-6.35), no close follow-up by health workers (AOR = 0.59;95% CI 0.39-0.88), regular antenatal care follow-up (AOR = 1.77;95% CI 1.23,2.58), health professionals lack of respect to clients (AOR = 2.32; 95% CI 1.45-3.79), and lack of health workers (AOR = 0.43;95% CI 0.29-0.61) were significantly associated with the utilization health behavior of institutional delivery service. Conclusion The prevalence of institutional delivery in the study area was low. The current study revealed that among the health belief model construct perceived susceptibility and cues to action were significantly associated with the utilization behavior of institutional delivery service. On top of that strong follow-up of the community and home based discussion was a significant factor for the utilization behavior of institutional delivery service.